INVESTIGASI ORIENTASI USAHA DAN PENGEMBANGAN MODEL PENGUATAN UNTUK USAHA KECIL DAN MENENGAH: SEBUAH KAJIAN EMPIRIK - Afifah, Afifah; Gustina, Gustina (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016)
West Sumatra is a province which is possess a variety of traditional food. Such foods have became souvenir icon for visitors who come to the tourist areas of West Sumatra. These kinds of food produced by Small and Medium Enterprises (SMEs) scattered throughout the territory of West Sumatra. Government group them into snack cluster. The purpose of this study was to investigate the affirmation model of snack SMEs in West Sumatra as well as to arrange simulation of the models designed. This is qualitative study implements Focus Group Discussion and in-depth interview as data collection method . The results show that snack SMEs in the sample region need to be reinforced through training, mentoring, and coaching. Training required include entrepreneurial and managerial skills.
Keywords: small and medium enterprise, snack cluster, affirmative model